Smart Healthcare Monitoring System Using Zigbee Protocol - Jagtap Aditya; Dolas Omkar; Gawade Atharv; Dr. Divekar S.N. (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In today’s fast-paced world, healthcare technology must evolve to provide accurate, real-time patient monitoring while ensuring user-friendliness and efficiency. This research explores a Zigbee-based human health monitoring system that leverages low-power wireless communication to integrate multiple biometric sensors. The proposed system gathers vital data such as heart rate, blood pressure, oxygen saturation, and electrocardiogram readings through wearable sensor modules. By processing these signals via an Arduino microcontroller and transmitting them over a mesh network, the system enables continuous remote monitoring and prompt alerting for abnormal physiological conditions. This approach not only enhances patient care but also significantly reduces the need for frequent hospital visits, thereby alleviating pressure on medical facilities. The study demonstrates a comprehensive blend of human-centric design and advanced engineering principles. Extensive experimental evaluations were conducted in realistic hospital environments to verify system reliability, performance, and energy efficiency. The findings reveal that the Zigbee-enabled architecture ensures robust data transmission with minimal power consumption, making it ideally suited for long-term monitoring applications in both clinical and field settings. The research provides compelling evidence for the integration of wireless sensor networks in healthcare, underscoring the potential for future innovations in remote patient care and telemedicine.